(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article provides a comparative analysis of the moral principles presented in Shaykh Muhammad Sodiq Muhammad Yusuf’s work “Ijtimoiy odoblar” (“Social Etiquette”) and contemporary moral norms in modern society. It examines how moral standards are changing today and considers the influence of globalization, digital technologies, and transformations in family structures. In addition, the Shaykh’s recommendations for strengthening moral values are analyzed from the perspective of addressing modern challenges.